Child Protection And Marriage Prevention - Fransiska Novita Eleanora; Andang Sari (Humani (Hukum dan Masyarakat Madani), 2019)
Recognition and protection of children's rights is fully a shared responsibility of both the parents, the government and the wider community that guarantees its survival and development and the growth of children in a strong, healthy and intelligent state. The main role in the development of children in addition to nutrition and vitamin intake or fulfillment of clothing, food and shelter, is also needed attention to the development of children in the future which is the right of the child to get education and teaching so that the aspirations can be achieved and succeed as he wants. But with the changing times it turns out that the rights of children are neglected in the sense that they are not fulfilled as expected, because they are triggered by economic factors so that children cannot attend school or continue  their  education  due  to  marriage  at  a  young  age  or  so-called  early marriage.  With  the  occurrence  of  marriage  at  a  young  age  for  children  is  a violation of the rights of children, and children experience the destruction of their future because they are not ready and mature thinking and psychology because basically children should be protected from any threat or anyone. Protection of children's rights is absolutely granted, and has been regulated in the child protection law and marriage law regarding the age limit of children, the fact that there is still a high level of child marriage. The research method that is used or used in this writing uses literature studies based on the literature of journals, books, magazines and even from legislation relating to child protection and child marriage. The results showed that economic factors are the dominant occurrence of early marriage and lack of awareness of parents and community members on the protection and prevention of child marriages, on the other hand there is the assumption that by marrying their children, the obligations of parents are completed and by carrying out the marriage live independently without depending on their parents. The involvement and participation of the government can also prevent early marriage, especially in the application of sanctions in the rules that have been set, because if you want to protect children's rights, one of them is to prevent early marriage, or in other words stop child marriage.